Development of a Digital Book Development of a Digital Book on the Local History of Tegal’s Origins to Strengthen Historical Consciousness of Senior High School Students in Tegal City - Mas Andi Novia Budi; Akhmad Arif Musadad; Leo Agung Sutimin (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to develop a digital book on the local history of Tegal’s origin as an effort to strengthen high school students’ historical consciousness. The background of this research stems from the lack of local history content in school history learning, which predominantly emphasizes national events. This condition results in students’ limited knowledge and low awareness of their local history. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through questionnaires, interviews, and expert validations by material and media specialists. The findings indicate that students responded positively to the need for digital learning materials based on local history. The developed digital book integrates text, images, and interactive multimedia, designed using Canva and Smart App Creator (SAC). Validation results showed scores of 96% from the material expert and 97% from the media expert, both categorized as “very good.” These results demonstrate that the digital book on Tegal’s origin is feasible as a learning medium and effective in supporting the enhancement of students’ historical consciousness. This research contributes to the development of digital-based.